Studies on the Stabilities of Some Mixed Ligand Complexes of Lanthanide(III) Ions - Varshney, Bhawna; Gupta, K.C. (Asian Journal of Chemistry, 2010)
Ternary complexes of lanthanides with CPTA as primary and quinaldic acid as a secondary ligand having the general formula [M-CPTA-quinaldic acid) where M = La(III), Sm(lll), Eu(lII), Gd(III) and Dy(III) have been described potentiometrically at different temperatures and at constant ionic strength μ = 0.2 M (KNO3) using the modified Irving and Rossotti's method. The thermodynamic parameters for the formation of the complex [M-CPTA-quinaldic- acid] have also been calculated. The stability constants show the following order Dy3+ < Sm3+ = La3+ < Eu3+ < Gd3+